2010
DOI: 10.2139/ssrn.1649678
|View full text |Cite
|
Sign up to set email alerts
|

Mother or Motherland: Can a Government Have an Impact on Educational Attainment of the Population? Preliminary Evidence from India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…To put maternal capital in context, it is helpful to also measure broader components of family capital—for example, economic capital—such as material assets and land ownership. Other studies have identified lower household socio‐economic position, especially in rural areas, with poor educational attainment (Bhaumik and Chakrabarty, ; Reed et al, ). These factors are less closely associated with maternal phenotype and are expected to have no opportunity to influence maternal development prior to marriage.…”
Section: Maternal Effectsmentioning
confidence: 93%
“…To put maternal capital in context, it is helpful to also measure broader components of family capital—for example, economic capital—such as material assets and land ownership. Other studies have identified lower household socio‐economic position, especially in rural areas, with poor educational attainment (Bhaumik and Chakrabarty, ; Reed et al, ). These factors are less closely associated with maternal phenotype and are expected to have no opportunity to influence maternal development prior to marriage.…”
Section: Maternal Effectsmentioning
confidence: 93%